Detection of 40 bp insertion-deletion (INDEL) in mitochondrial control region among sambar (Rusa unicolor) populations in India. (December 2015) - Gupta, Sandeep; Kumar, Ajit; Gaur, Ajay; Hussain, Syed
Abstract Background The mitochondrial DNA (mtDNA) control region is extensively used in the phylogeography of species. We examined sequence variations in the mtDNA control region of sambar (Rusa unicolor ) populations from the South, Central and North India. Results Most of the samples collected from the south India exhibited a 40 bp insertion in the mtDNA control region. This insertion was not observed in the North and Central Indian populations. Conclusion This study provided a potential marker for molecular screening and identification of sambar populations in the form of a distinct 40 bp insertion. Some populations in South India did not exhibit this insertion. It indicates that there could be an ecological barrier that might be preventing the expansion of insertion-positive sambar population.